Analysis of Factors Influencing Consumer Behavioral Intention towards Lifestyle Feature on Indonesian Mobile Banking - Hermawan, Dimas; Maria Apsari Sugiat (Universitas Medan Area, 2024)
Banking companies are actively pursuing digital transformation to increase market share and meet customer needs. One such initiative is the integration of lifestyle features within mobile banking plat-forms. However, these efforts are challenged by low adoption rates and customer resistance. This research aims to determine the factors that affect consumers' decisions to embrace “Sukha” as a lifestyle feature. The research framework utilized a modified UTAUT-2 with purposive sampling techniques and GPower software; a total of 177 respondents were obtained. Based on analysis using the Structural Equa-tion Model – Partial Least Square (SEM-PLS), it was found that Habit, Epistemic Value, and Perceived Security have a positive and significant influence on the inclination to use, and the intention to use Sukha have a positive and significant influence on its use. Through Multi Group Analysis, it was found that age, income, and gender generally do not significantly impact the desire to use the features. In the end, this study implies that the banking sector needs to foster habitual use among customers by choosing the appropriate merchants, consistently guaranteeing transaction security, and stimulating consumer curiosity with popular or trending services.